Implementation of Environmental Education in the Concept of Ecotawhid and Ecotheology in Students - Suraijiah, Suraijiah; Rusdiah, Rusdiah; Surawardi, Surawardi (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study aims to explore and analyze the implementation of environmental education grounded in the concept of ecotauhid (Islamic ecotheology) among students at the Darul Hijrah Putera Martapura Islamic Boarding School. This research focuses on identifying how ecotahyd values are integrated into educational activities and how this approach contributes to shaping students' ecological awareness and character. The novelty of this research lies in its emphasis on ecota-tawheed as a holistic framework that unites beliefs, knowledge, and environmental responsibility within the pesantren context. This qualitative study uses observation, interviews, and documentation to examine forms of environmental education, which include: (1) Curricular, through Aqidah Akhlak, Fiqh, and Islamic Religious Education subjects that contain values based on ecotauhid; (2) Co-curricular, through enrichment activities such as fisheries, agriculture, and reforestation; and (3) Extracurricular, through the Adiwiyata program that promotes environmental protection and appreciation. The development of the Eco Pesantren and Agrosilvofishery programs shows the integration of religious practices with environmental sustainability. This study concludes that ecotauhid-based education increases students' ecological awareness while fostering a religious, independent, and competitive generation.